Glaucoma, Parkinson's disease and neurodegeneration - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2015)
Glaucoma is a disease that causes irreversible vision loss characterized by progressive retinal ganglion cell (RGC) death. The mechanisms independent of intraocular pressure are also implicated in glaucomatous degeneration pathogenesis and numerous similarities exist between glaucoma and neurodegenerative diseases such as Alzheimer's and Parkinson's diseases. Although, there is a common pathway between glaucoma and neurodegenerative disorders, pathogenesis of the relationship between neurodegenerative disorders and glaucoma remains poorly undefined. Optical coherence tomography (OCT), non-invasively quantifies the thickness of the retinal nerve fiber layer (RNFL) which is effected due to RGC damage in glaucomatous patients. Recently, RNFL thickness measurements have been studied by using OCT in several neurodegenerative conditions, including Parkinson's disease. The RNFL is unique as a model of neurodegeneration where the changes in its structure is represented with axonal damage. RNFL thickness measurements are important in neurodegenerative disorders which are characterized with neuronal loss and have common pathogenesis with glaucoma. In this review, we emphasize the relationship between glaucoma, Parkinson's disease and neurodegeneration.
Keywords: Irreversible vision loss; Neurodegenerative disorders; Neuroprotective therapy; CELL APOPTOSIS; EXPRESSION; GLUTAMATE; DOPAMINE; RETINA; MODELS; DEATH